Acoela (Acoelomorpha) from the northern beaches of the state of Sao Paulo, Brazil, and a systematic revision of the family Otocelididae - Hooge, Matthew D.; Rocha, Carlos E. F. (Zootaxa, 2006)
Twenty-one species of Acoela, including seven new species and one new subspecies, are reported from the northern coast of the state of São Paulo, Brazil. The species include two from the family Actinoposthiidae (Philactinoposthia coneyi sp. nov., P. stylifera brasiliensis subsp. nov.), three from Convolutidae (Amphiscolops evelinae, Convoluta henseni, Heterochaerus sargassi), three from Haploposthiidae (Haplogonaria sophiae sp. nov., Kuma albiventer, K. asilhas sp. nov.), eight from Isodiametridae (Archaphanostoma marcusi sp. nov., Avagina marci, Isodiametra divae, I. vexillaria, I. westbladi, Pseudaphanostoma divae, P. herringi sp. nov., Unnamed Species 1), one from Mecynostomidae (Eumecynostomum evelinae), three from Otocelididae (Haplocelis dichona, Otocelis erinae, sp. nov., Philocelis robrochai sp. nov.) and one from Paratomellidae (Paratomella rubra). The genera Haplocelis and Otocelis from the defunct family Otocelididae are reassigned to the family Isodiametridae.